The Impact of E-procurement Adoption on the Performance of Government Agencies. Mukono Municipality - Phoebe Namugoya (Uganda Christian Uganda, 2024)
This study also investigated the impact of eprocurement adoption on organizational performance in Mukono Municipality, considering e-invoicing, e-tendering, and e-sourcing. After thorough analysis, based on the responses by 42 participants, it emerged that e-invoicing has considerably streamlined inventory management through gains in tracking and visibility, though not without challenges in training and integration at different levels. Although etendering has assisted in shortening the lead times, there is still some overlap regarding the evaluation of bids and posting of communication. Much more development should be done to the system to trim these unwanted issues. Basheka & Bisangabasaija 2018. E-sourcing has also improved communication with suppliers and the management of their relationships. However, accuracy of data and conflict resolution remains some of the issues. The results showed that while the e-procurement systems presented significant benefits, securing full effectiveness will require further, focused improvements related to training, system features, and process optimization. This research has added to the knowledge base of the impacts of e-procurement on municipal procurement processes and provided practical recommendations for system performance improvements.
Undergraduate Dissertation